Leishmaniasis, An Emerging Disease Found in Companion Animals in the United States - Petersen, Christine A. (2009)
This review discusses leishmaniasis in cats and dogs in the United States. Leishmaniasis is endemic in Foxhound populations in the United States and is still being characterized in this group. Pathophysiology, clinical signs, transmission, immunology, and treatment are examined in this review. Leishmaniasis is an emergent zoonosis of great public health significance.